Phosphonated graphene oxide with high electrocatalytic performance for vanadium redox flow battery - Etesami, M. (Elsevier Ltd, 2018)
Development of more efficient electrodes is essential to improve the competitiveness of vanadium redox flow battery (VRFB) systems. Covalent functionalization of carbon structure in graphene oxide with phosphonic acid groups was carried out to enhance the electrode wettability. The phosphonated graphene oxide (P-GO) was characterized and found displaying an improved electrocatalytic performance towards electrooxidation/electroreduction of vanadium ion pairs. The defect in P-GO structure increased the negative charge density on the surface leading to higher vanadium ions tendency for electrooxidation/electroreduction reactions. The battery performance was evaluated using electrodes made of carbon felt hosted GO and P-GO in a single cell VRFB and 180 charge-discharge cycles were recorded. The VRFB with P-GO displayed an improved performance and stable coulombic, voltage and energy efficiency compared to VRFB with GO. Â© 2017 Hydrogen Energy Publications LLC